Neuropsychobiological Fingerprints of Chronic Fatigue in Sarcoidosis - Kettenbach, Sarah; Radke, Sina; Müller, Tobias; Habel, Ute; Dreher, Michael (Frontiers in Behavioral Neuroscience, 2021)
Background: Chronic fatigue is a prominent symptom in many sarcoidosis patients, affecting quality of life and interfering with treatment. This study investigated neuropsychobiological mechanisms and markers of chronic fatigue in sarcoidosis. Methods: Thirty patients with a histological diagnosis of sarcoidosis were included. The Multidimensional Fatigue Inventory was used to define patients with and without chronic fatigue. All patients were then characterized using several depression, quality of life and executive functioning questionnaires. Cognitive functioning and underlying neural correlates were assessed using an n-back task measuring working memory and (sustained) attention during functional magnetic resonance imaging. Sarcoidosis disease activity was determined using lung function, laboratory parameters, and exercise capacity. Results: Nineteen patients had chronic fatigue and 11 did not; both groups had similar demographic and disease activity characteristics. Chronic fatigue patients showed more symptoms of depression and anxiety, and lower quality of life. During the n-back task, chronic fatigue was associated with a smaller increase in brain activation with increasing task difficulty versus the group without fatigue, especially in the angular gyrus. Conclusion: Inadequate adjustment of brain activation with increasing demands appears to be a potential neurobiological marker of chronic fatigue in sarcoidosis patients. The angular gyrus, which plays an important role in working memory system, was the major area in which fatigue patients showed smaller increase of brain activation compared to those without fatigue. These findings might be relevant for a deeper understanding of chronic fatigue mechanisms in sarcoidosis and future clinical treatment of this disabling syndrome.